2017
DOI: 10.1007/s10571-017-0469-1
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Protects PC12 Neuronal Cells against H2O2-induced Cytotoxicity and Oxidative Stress via a ROS-dependent Up-regulation of Endogenous Antioxidant System

Abstract: Sinomenine (SN), a purified alkaloid from Chinese herb Sinomenium acutum that was used preferentially in the treatment of rheumatoid diseases, has exerted neuroprotective effects and anti-inflammatory properties in many previous studies. Some studies have revealed that the antioxidant property of SN, acting mainly through inhibiting NADPH oxidase activation, was involved in the beneficial effects of SN. However, SN belongs to the family of dextrorotatory morphinan analogues, which may initiate elevation of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The present study investigated the effects of SIN on AS, and an AS mouse model was created and treated with different concentrations of SIN (10, 30, and 50 mg/kg). Because pro-inflammatory cytokines and oxidative stress are involved in the development of AS, and because SIN has anti-inflammatory and antioxidant effects [ 18 , 32 , 33 ], the study determined the markers of inflammation (TNF-α, IL-1β, and IL-6) and oxidative stress (SOD, CAT and GSH-PX), showing that AS mice had higher levels of TNF-α, IL-1β, and IL-6, and lower levels of SOD, CAT, and GSH-PX. SIN treatment reduced the levels of TNF-α, IL-1β, and IL-6 in a dose-dependent manner, and the levels of SOD, CAT, and GSH-PX were dose-dependently increased.…”
Section: Discussionmentioning
confidence: 99%
“…The present study investigated the effects of SIN on AS, and an AS mouse model was created and treated with different concentrations of SIN (10, 30, and 50 mg/kg). Because pro-inflammatory cytokines and oxidative stress are involved in the development of AS, and because SIN has anti-inflammatory and antioxidant effects [ 18 , 32 , 33 ], the study determined the markers of inflammation (TNF-α, IL-1β, and IL-6) and oxidative stress (SOD, CAT and GSH-PX), showing that AS mice had higher levels of TNF-α, IL-1β, and IL-6, and lower levels of SOD, CAT, and GSH-PX. SIN treatment reduced the levels of TNF-α, IL-1β, and IL-6 in a dose-dependent manner, and the levels of SOD, CAT, and GSH-PX were dose-dependently increased.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that SIN has antioxidant activity in different cells [ 27 , 28 ]. The Nrf2 signaling pathway is the major defense against inflammatory responses and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is also used to examine the resistance of flies against OH − ‐induced oxidative stress (Fan et al, ). Flies were maintained on their corresponding control diet or phlorizin diet at 25°C for 25 days.…”
Section: Methodsmentioning
confidence: 99%